Vulnerability of the population of Guerrero state, Mexico, to COVID-19 and dengue epidemics. - Peña-Galeana, Norma Ivone (2021)
The present article analyzes the situation of COVID-19 and dengue in the municipalities of the state of Guerrero, Mexico, as well as the situation of affected population groups classified by age and sex. Factors associated with prevention and control measures of both epidemics are also analyzed, including: availability of potable piped water, food sufficiency for minors and adults, and affiliation to health care services. Likewise, based on the aforementioned factors, a classification of the municipalities comprising the state of Guerrero is made according to the population’s level of vulnerability to both epidemics as a whole. Vulnerability is defined as the susceptibility of the population to be affected by COVID-19 and dengue given the situation of the studied factors.